Competencia laboral del Tribunal Electoral del Poder Judicial de la Federación - Guzmán Díaz, Alfredo (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
It is important to present this work and stimulating legal research since the electoral law in the past twenty five years has an important place in Mexico in the academic training of the lawyer profession. Its importance lies in the fact that its continuous change through reforms of the state, requires permanent study further to understand the changes in the institutions of the political system, electoral and legal systems governing elections. In October 1990, he became one of the most important reforms and the transformation of the political system that caused traumatic elective process and questioned as 1988, creating a new electoral legislation, the Federal Code of Institutions and Electoral Procedures and institutions were founded as the Federal Electoral Tribunal, the Federal Electoral Institute and inside the Professional Electoral Service, but also entail a sui generis originated employment relationship; and resolution of labor disputes2. Article 99 Constitutional reformed totally, for the purposes set forth therein: "The Electoral Court shall, except as provided in Section II of Article 105 of the Constitution, the highest judicial authority in the matter and specialized organ of the Judicial Power of the Federation ..." The agency was responsible for organizing until 2012 federal elections, was refounded by the federal legislator and created the April 4, 2014, the National Electoral Institute that the June 7, 2015; by constitutional mandate, I had the responsibility to "organize the elections it is a state function," but in the aforementioned constitutional reform, did not change as indicated in article 99, section VII of the Constitution of the United Mexican States.

Resulta importante y estimulante presentar este trabajo de investigación jurídica ya que el derecho electoral en los últimos cinco lustros ocupa un lugar importante en México en la formación académica de la profesión de abogado. Su importancia radica en el hecho de que su continua modificación, vía las reformas del Estado, exige su permanente estudio además de entender los cambios en las instituciones del sistema político, las electorales y los ordenamientos legales que regulan los procesos electorales. En octubre de 1990, se dio una de las reformas más importantes y la transformación del sistema político que propició procesos electivos traumáticos y cuestionados como el de 1988, creándose una nueva legislación electoral, el Código Federal de Instituciones y Procedimientos Electorales y se fundaron instituciones como el Tribunal Federal Electoral, el Instituto Federal Electoral y a su interior el Servicio Profesional Electoral, pero también aparejado se originó una sui generis relación laboral; y resolución de conflictos laborales.1 El artículo 99 Constitucional se reformó de manera total, para los efectos que en él se establece: “El Tribunal Electoral será, con excepción de lo dispuesto en la fracción II del artículo 105 de esta Constitución, la máxima autoridad jurisdiccional en la materia y órgano especializado del Poder Judicial de la Federación...” El organismo que se encargó de organizar hasta el año 2012 las elecciones federales, fue refundada por el legislador federal y creó el 04 de abril de 2014, al Instituto Nacional Electoral que el 07 de junio de 2015; por mandato constitucional, tuvo la responsabilidad de “organizar las elecciones que es una función estatal”, pero en la referida reforma constitucional, no se modificó lo indicado en el artículo 99 fracción VII de la Constitución Política de los Estados Unidos Mexicanos.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2015-1628; Tribunal; Electoral; Federación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/677